(untitled) (Innovative professional education, 2025)
The article is devoted to studying the possibilities of using interactive digital tools in the teaching of chemistry at vocational education institutions. It explores the advantages and features of virtual chemical laboratories, interactive simulations, online interactive whiteboards, and collaborative platforms. The article also analyzes the impact of these tools on increasing motivation, engagement, and the quality of chemical knowledge acquisition among students in various professional fields. The benefits and challenges of implementing these technologies are discussed, along with prospects for their further development.